PENGARUH KEPUASAN KERJA, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN KSP CREDIT UNION DHARMA PRIMA KITA SLEMAN - Zulfan Saputra Pratama Pegia; Audita Nuvriasari (Departemen Manajemen, 2021)
This study aims to analyze the effect of work, work environment, and compensation both partially and simultaneously on the employee turnover intention of KSP Credit Union Dharma Prima Kita. This research was conducted with a quantitative approach. The sampling technique used purposive sampling with the sample criteria is a minimum employee work period of 1 year. The sample in this study was 60 respondents. The results showed that partially job satisfaction, work environment, and had a negative and significant effect on turnover intention, with a significant level (p) 0.05. Job satisfaction, work environment, and compensation simultaneously have a negative and significant effect on turnover intention. The variable that most dominantly affects turnover intention is job satisfaction.